An Exploration of the needs of a Cardiac Rehabilitation Population using a Subjective Quality-of-Life Measure - Basquille, Emily; McKenna, Verna; Houlihan, Ailish; Molony, Kate; McInerney, Dr. Veronica; Mannion, Dr. Eileen; Barton, Dr. John; Waldron, Prof Dympna (International Journal of Innovative Research in Medical Science, 2020)
Context: The aim of this study was to profile a cardiac rehabilitation population in the West of Ireland and establish Subjective Quality of Life (SQoL), using The Schedule for Evaluation of Individual Quality of Life-Direct Weighting (SEIQoL-DW), a validated subjective QoL measure. Bothersome symptoms (SB) and Symptom Interference in SQoL (SBIQoL) were also assessed using a using a modified SEIQoL-DW. Objectives: QoL is a difficult concept to define, therefore the medical profession often premise QoL on health and illness. The focus of this study was to explore the QoL needs of a cardiac population, with a view to informing the development of a newly formed cardiac rehabilitation support group. The SEIQoL-DW was developed to overcome the limitations of quantitative questionnaires, as it is based on the individual’s personal view of life and its quality. Methods: SQoL, symptoms and SBIQoL, of 22 individuals, who had suffered a cardiac event were explored. SEIQoL-DW is a semi-structured interview, enabling the individual to convert their perspectives into scientific values. QoL areas of importance to patients are called ‘cues’. A modified SEIQoL-DW was used to assess SB and SBIQoL. Data were analysed using both quantitative analysis and qualitative descriptive analysis. Findings: Participants highlighted a range of QoL cues; findings from this study showed that 45% of participants did not rate ‘health’ in the first five QoL cues. A significant number of participants experienced symptoms; a medium negative correlation was found between symptom interference and QoL, rho = -0.353, with high levels of symptom interference associated with low levels of QoL. Conclusions: The range of QoL cues and bothersome symptoms identified in this study had implications for the development of the group, with participants eager to participate and talk candidly about their needs. SEIQoL-DW proved to be an acceptable, reliable and valid technique for measuring both individual QoL, SB and SBIQoL, taking greater consideration of individual perspectives compared with traditional measurement approaches. The significance of nominated symptoms and SBIQoL warrants further attention, especially if these symptoms are reversible.